The Effect of Operating Costs on Environmental Degradation under International Environmental Standards: Case study - Khartoum State - Mahmoud, Abdelmotalab Osman; Mohamed, Asim Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2020)
This research aimed to determine the extent to which operating costs affect the environmental degradation in the Khartoum State, under the international environmental standards. In order to reach such objective, (45) questionnaire forms have been distributed to the research community respondents, who represent a random sample of the employees working at the Higher Council for Environment at the Khartoum State in 2019. To effect the data analysis, the Statistical Package for the Social Sciences program has been used. The research, on the other hand, used the analytical descriptive approach to effect the field study. Based on said account, the research has reached a number of findings, the most significant of which, are the following: the purchase of old machinery causes the state to incur enormous losses. Lack of sufficient environmental awareness from the part of the native has increased the depreciation of the machinery. Poor finance has led to halt the machinery. The research concluded with a set of recommendations, including the following: the research recommended raising the environmental awareness of the native, in order to reduce the depreciation of the machinery. The research recommended providing necessary finance to continuously operate the machinery.
Keywords: international standards; environmental degradation; global warming; sustainable development; ozone hole